Combined Morphological and Palynological Classification for Hibiscus syriacus L. (Malvaceae): Construction of the Diagnostic Classification Framework and Implications of Pollen Morphological Variation on Fruiting - Fen Xiao; Xiaohong Wang; Yun Jiang; Chulin Chen; Jiajia Chen; Jingwen Zhang; Yafeng Wen (Agronomy, 2023)
Identifying useful taxonomic indicators for classifying Hibiscus syriacus L. (Malvaceae) cultivars can help address challenges in their homonymy and synonymy. Moreover, analyzing which pollen traits possibly lead to their successful fruiting can serve to guide the hybridization and breeding of H. syriacus. For the first time, this study classified 24 cultivars of H. syriacus based on 24 morphological and palynological indicators assessed for flowers, leaves, and pollen grains. These indicators were a mixture of quantitative and qualitative traits, measured to contribute to the identification and classification of H. syriacus cultivars. The results showed that the 24 H. syriacus cultivars could be classified into 2–6 clusters according to different taxonomic criteria. The leading diagnostic indicators were eight quantitative and eight qualitative traits, of which two new quantitative traits—the width of the spine base (SW) and average of the pollen grain radius and spine length (D-spine)—and five new qualitative traits—the amount of pollen surface spines (O-SA), whether the petals have the red center (B-RC), whether the pollen surface ruffles strongly (B-RS), the degree of pollen surface ruffling (O-DR), and relationship between calyx and bract (O-CB)—could be used as defining traits for H. syriacus cultivars owing to their robust contribution to the classification. The correlations between indicators for flowers, leaves, and pollen grains were explored, which revealed that the O-SA in H. syriacus was strongly tied to quantitative pollen traits. Furthermore, three qualitative morphological traits—whether the stamens are heterogeneous in terms of inner petals (B-IP), O-CB, and whether the leaf lobing is strong (B-LL)—were correlated with partial quantitative pollen traits. We also found that those H. syriacus cultivars with micro-spines or granulate on the pollen grain surface have higher fruiting rates; additionally, pollen diameter, spine length, and spine spacing might also be potential factors influencing successful breeding. The insights gained from this study could fill a key knowledge gap concerning the taxonomic criteria suitable for distinguishing H. syriacus cultivars. Our findings also provide timely information on how to understand the pollination process, especially those aspects leading to pollinator selection via pollen grain features, which could influence breeding programs and outcomes.